2014
DOI: 10.1007/s11418-014-0836-x
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of a Platycodon root extract on ultraviolet B-induced pigmentation due to a decrease in Kit expression

Abstract: The signaling of stem cell factor (SCF) through its receptor Kit is known to play an important role in regulating cutaneous melanogenesis. In the course of UVB-induced pigmentation, the expression of membrane-bound SCF by epidermal keratinocytes is upregulated at an early phase and subsequently activates neighboring melanocytes via their Kit receptors. In order to identify effective skin-lightening materials, we screened botanical extracts to determine their abilities to diminish Kit expression in melanocytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, GlcCer ( 3 ) did not suppress melanogenesis, melanogenic protein expression, or ATP levels in normal melanocytes. In the present study, we selected α‐MSH to induce melanogenesis because a previous study demonstrated that a co‐stimulation with ET‐1 and SCF (Kasamatsu et al, 2014) did not induce melanogenesis. Therefore, 14 did not exhibit anti‐melanogenic activity against α‐MSH‐induced melanogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, GlcCer ( 3 ) did not suppress melanogenesis, melanogenic protein expression, or ATP levels in normal melanocytes. In the present study, we selected α‐MSH to induce melanogenesis because a previous study demonstrated that a co‐stimulation with ET‐1 and SCF (Kasamatsu et al, 2014) did not induce melanogenesis. Therefore, 14 did not exhibit anti‐melanogenic activity against α‐MSH‐induced melanogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A paracrine linkage has been reported between keratinocytes, fibroblasts, and melanocytes. Several cytokines and chemokines such as SCF, α MSH, histamine, endothelin -1 and prostaglandins were found to be released from epidermal keratinocytes in response to ultraviolet B rays exposure (Kasamatsu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of tyrosinase essential for melanogenic cascade can be stimulated by UVB exposure that further increases melanin synthesis required for UVB-induced delayed tanning [5]. The membrane-bound stem cell factor is up-regulated and then activates neighboring melanocytes through kit receptors in the course of UVB-caused pigmentation [6]. Nrf2 (nuclear factor, erythroid 2-like 2) may exert protective effects on an inflammation and a sunburn reaction that were induced by UVB exposure via inhibiting inflammation and extracellular matrix degradation [7].…”
Section: Introductionmentioning
confidence: 99%